Bioinformatics analysis of cis-regulatory elements in Mbl1 and Mbl2 genes in Rattus norvegicus - Bondarenko, V.S.; Obolenska, M.Yu. (2015)
Aim. To identify and characterize with the help of bioinformatics the transcription factors binding sites in promoters of Mbl1 and Mbl2 genes, encoding mannose binding lectins in Rattus norvegicus. Methods. Bioinformatics, MatInspector software. The position weight matrices of transcription factor binding sites were obtained from the Matrix Family Library Version 9.0. Within the frame of the program we selected the binding sites, the cognate transcription factors of which are specifically expressed in the liver and immune cells, and have passed the filter for conservation after comparison with the binding sites in orthologous genes in Mus musculus. Results. The promoters of both genes share the binding sites for the members of the four common families of transcription factors (HNF, homeodomain transcription factors, GRs and ETS factors). The promoters of Mbl1 and Mbl2 gene possess correspondingly additional binding sites for the members of six (AP1 related factors, Ccaat/Enhancer Binding Proteins, FOX, p53, NFAT, ISGF3) and four (cAMP-responsive element binding proteins, heat shock factors, Nf-?B/c-rel and TATA binding protein) families of transcription factors. The Mbl1 specific transcription factors are mainly involved in the regulation of differentiation, development, metabolic homeostasis, organogenesis and cell cycle. Unlike them the Mbl2 specific transcription factors are more prone to mediate a stress-response. Conclusion. The variety of transcription factors potentially involved in regulation of the Mbl1 and Mbl2 transcription argue for these genes involvement in various cellular processes with specific role of each gene. The obtained results provide the basis for the task-oriented wet-lab bench experiments on their regulation. Мета. Провести біоінформатичне дослідження промоторів генів Mbl1 і Mbl2 Rattus norvegicus, що кодують манозозв’зуючий лектини, на наявність та функціональну специфічність сайтів зв’язування транскрипційних факторів. Методи. Обидві послідовності промоторів довжиною 1100 п.н. проаналізовано в програмі MatInspector за використання позиційно-вагових матриць з бази данних Matrix Family Library Version 9.0. В межах програми відібрано сайти зв’язування для транскрипційних факторів, які специфічно експресуються в печінці і клітинах імунної системи, а також, що пройшли тест на консервативність через порівняння з сайтами зв’язування транскрипційних факторів в промоторах генів – ортологів Mus musculus. Результати. В промоторах гена Mbl1 і гена Mbl2 наявні сайти для чотирьох родин транскрипційних факторів (HNF, homeodomain transcription factors, GRs and ETS factors). В промоторі гена Mbl1 виявлено також сайти для представників шістьох (AP1 related factors, Ccaat/Enhancer Binding Proteins, FOX, p53, NFAT, ISGF3), а в гені Mbl2 — для чотирьох (cAMP-responsive element binding proteins, heat shock factors, Nf-?B/c-rel and TATA binding protein) інших родин транскрипційних факторів. Характерні для гена Mbl1 транскрипційні фактори переважно задіяні в регуляції диференціювання, розвитку, підтримання гомеостазу, клітинного циклу. Через характерні для гена Mbl2 сайти транскрипційні фактори можуть опосередковувати переважно відповідь на чинники, які індукують стрес. Висновок. Різноманітність транскрипційних факторів, які потенційно можуть регулювати транскрипцію обох генів, вказує на можливу участь генів в різних клітинних процесах зі специфічною функцією кожного з генів. Отримані результати є підставою для цілеспрямованого експериментального дослідження регуляції транскрипції зазначених генів. Цель. Провести биоинформатическое исследование промоторов генов Mbl1 и Mbl2 Rattus norvegicus, кодирующих монозосвязывающий лектины, на наличие и функциональную специфичность сайтов связывания транскрипционных факторов. Методы. Обе последовательности промоторов длиной 1100 п.н. проанализированы в программе MatInspector за использование позиционно-весовых матриц из базы данных Matrix Family Library Version 9.0. В рамках программы отобрано сайты связывания для транскрипционных факторов, которые специфически экспрессируются в печени и клетках иммунной системы, а также, что прошли тест на консервативность через сравнение с сайтами связывания транскрипционных факторов в промоторах генов - Ортолога Mus musculus. Результаты. В промоторах гена Mbl1 и гена Mbl2 имеющиеся сайты для четырех семей транскрипционных факторов (HNF, homeodomain transcription factors, GRs and ETS factors). В промоторе гена Mbl1 обнаружено также сайты для представителей шести (AP1 related factors, Ccaat / Enhancer Binding Proteins, FOX, p53, NFAT, ISGF3), а в гене Mbl2 - для четырех (cAMP-responsive element binding proteins, heat shock factors, Nf -? B / c-rel and TATA binding protein) других семей транскрипционных факторов. Характерные для гена Mbl1 транскрипционные факторы преимущественно задействованы в регуляции дифференцировки, развития, поддержания гомеостаза, клеточного цикла. Из-за характерных для гена Mbl2 сайты транскрипционные факторы могут опосредовать преимущественно ответ на факторы, которые индуцируют стресс. Вывод. Разнообразие транскрипционных факторов, которые могут регулировать транскрипцию обоих генов, указывает на возможное участие генов в различных клеточных процессах со специфической функцией каждого из генов. Полученные результаты являются основанием для целенаправленного экспериментального исследования регуляции транскрипции указанных генов.